Courts of appeal, bureaucracies and conditional project permits: The role of negotiating non-exclusive property rights over the environment - Ernst Mohr (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1990)
Much of what may be coined the creeping degradation of the environment is due to economic projects which are subject to public approval. The erection of buildings, the siting of factories, all require permission from bureaucracies. To answer the question whether there is too much or not enough of the environment thus requires an analysis of the criteria under which private projects are publicly approved. An omnipotent and benevolent dictator will undertake an environmentally sensitive project under the safeguards of an optimal emission control if the public environmental costs are exceeded by the private net gains from the project, or so the story goes. To continue the tale, a benevolent bureaucracy possessing absolute authority over the use of the environment will permit projects, given optimal safeguards, if the same condition is fulfilled.
Keywords: 330; Umweltökonomik; Verhandlungen; Eigentumsrechtstheorie; Bürokratie; Theorie